THE IMPACT OF DIGITAL BANKING ON CUSTOMER LOYALTY IN ISLAMIC BANKS IN INDONESIA - Amanda Frizka (GREET, 2025)
This study examines how digital banking influences customer loyalty in Islamic banks in Indonesia, where technology adoption must comply with Shariah principles. Using a mixed-methods design, data were collected from a survey of 500 customers and interviews with 30 respondents. Regression analysis shows that digital banking adoption has a significant positive effect on loyalty, with service quality, ease of use, transaction security, and accessibility emerging as the strongest drivers. The results also highlight the unique role of Shariah compliance and ethical practices in building trust and sustaining customer relationships. Younger generations, particularly millennials and Gen Z, demonstrated stronger loyalty toward banks offering seamless mobile applications and personalized digital services. The findings contribute to the literature by extending the study of digital banking beyond conventional finance and into the underexplored Islamic banking sector. Practically, the study suggests that Islamic banks must integrate advanced digital features with Shariah-compliant values to secure long-term loyalty. Investment in cybersecurity, user experience, and innovative ethical financial products will be critical for achieving sustainable competitive advantage in the digital era.